Sustainability of Dialecticity in the City: The Perspective of the Emic Narrative Constructor - Aliūkaitė, Daiva (Respectus Philologicus, 2020)
The paper approaches the dialect-exploratory discourse, which concerns the interpretation of sustainability of dialecticity in the city. The given research aims at the evaluation of the sustainability of dialecticity in the city by performing the analysis of the emic narrative, i. e. the narrative of an ordinary member of the language community. In the city zones, the natural horizontal language continuum is disturbed; hence, from the perspective of etic, or the researcher, the problem of the co-existence, competition, levelling, etc. of different regional variants arises. What regards the emic perspective and the methodological inventory allowing for its formation, it should be stressed that it concerns the identification of the dialecticity conditions, or conditions determining variability that includes dialects. The emic narrative, or in other words, the I think that ... narrative, when reconstructed based on the empirical material collected for the research in perceptual dialectology embracing three Lithuanian cities, gives a piece of proper information to model the here and now and, to some extent, the future dialecticity projections. When discussing the problem of sustainability of dialecticity, the author concentrates on the segments of the reconstructed emic narrative that cover the reflection of language behaviour, estimation of language environment and a priori language attitudes toward the use of dialect codes.
Keywords: sustainability of dialecticity; emic narrative; an ordinary member of the language community; perceptual dialectology; city